Sustainable entrepreneurship: A strategic orientation approach for fostering sustainable development in Thai SMEs - Suk-Udom, Cholawit; Lekmat, Laddawan (Edelweiss Applied Science and Technology, 2025)
This research aims to investigate the interplay between leaders’ sustainability competencies, entrepreneurial orientation (EO), sustainability orientation (SO), and firm performance in Thai SMEs. Using a quantitative approach, data were collected from 385 SME owner-managers and analyzed through Structural Equation Modeling (SEM). The findings reveal that EO directly influences economic performance and indirectly affects environmental and social performance through SO. Leaders’ sustainability competencies predict SO, and EO forecasts economic, environmental, and social outcomes through economic results and SO. The results underscore the importance of integrating EO with SO to achieve comprehensive sustainability outcomes across economic, environmental, and social dimensions. This research contributes to the literature by offering an empirical model that links leadership competencies, EO, and SO to triple bottom line performance. Practically, the study provides actionable insights for SME leaders and policymakers, emphasizing the need to develop sustainability competencies and adopt a dual strategic orientation to foster long-term resilience and competitiveness. These findings are particularly relevant for emerging economies aiming to align entrepreneurship with sustainable development goals.